Between Flesh and Algorithm: Resistance Strategies in Brazilian Camming - Alencastro Veiga, Maria Júlia (AoIR Selected Papers of Internet Research, 2026)
This research examines how Brazilian camgirls develop techno-corporeal practices that simultaneously incorporate and resist platform capitalism's logics of abstraction. Drawing on Sobchack's concept of embodiment and Paasonen's carnal resonances, we investigate how performers navigate increasingly restrictive platform governance while creating affective connections through their bodies. Through a qualitative methodology triangulating virtual ethnography, interviews with ten Brazilian camgirls, and walkthrough analysis of platforms, this study reveals three key findings. First, performers develop embodied technical knowledge that enables them to circumvent platform control mechanisms, including multi-platform presence despite exclusivity requirements. Second, in response to high commission rates and payment barriers on mainstream platforms, camgirls create parallel economic systems using Brazil's state-managed PIX payment infrastructure, circumventing both platform commissions and dollar-based payment systems that many local consumers resist using. Third, these practices constitute forms of "regulated embodiment"—a condition where performers must balance platform compliance with embodied resistance. The Brazilian context reveals a distinctive dynamic where the state-managed payment system provides an infrastructural alternative to corporate financial intermediaries that routinely engage in financial deplatforming of sex workers. By examining how bodies become sites where platform governance, affective labor, and resistance converge, this research contributes to understanding embodied digital labor in the global south.